2016
DOI: 10.9767/bcrec.11.2.543.170-175
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Cationic Polyacrylamide Composite Catalyzed by An Ecologically Catalyst Clay Called Maghnite-H+ (Algerian MMT) Under Microwave Irradiation

Abstract: In this study, a novel green cationic hydrogel of cationic polyacrylamide composite have been prepared and investigated. The synthesis of green cationic polyacrylamide composite was evaluated for its solubility in water. The reactions were performed using acrylamide monomer, solvent, catalyst (clay fin called maghnite) and solution of H2SO4 (0.25 M), with the system under microwave irradiation (160 ºC) for 4 min. Major factors affecting the polymerization reaction were studied with a view to discover appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In the 1HNMR spectra of copolymer (PANI-PEO 2000 ), a wide signal in the region of 6.8-8 ppm was assigned to benzenoid hydrogen of polyaniline [39]. Three peaks in these region were assigned to para position of polyaniline linked for the polymerization.…”
Section: Spectroscopy Characterizationmentioning
confidence: 99%
“…In the 1HNMR spectra of copolymer (PANI-PEO 2000 ), a wide signal in the region of 6.8-8 ppm was assigned to benzenoid hydrogen of polyaniline [39]. Three peaks in these region were assigned to para position of polyaniline linked for the polymerization.…”
Section: Spectroscopy Characterizationmentioning
confidence: 99%
“…There are several methods for the synthesis of ZnO nanoparticles including precipitation in solution [2], spray pyrolysis [3], hydrothermal synthesis [4], and sol-gel processes [5]. Hydrothermal growth methods are frequently correlated with long growth times, normally 10 h or greater using conventional hot-plate methods [7,8]. Microwave heating is able to reduce the growth length to minutes while maintaining good morphology and ZnO crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating is able to reduce the growth length to minutes while maintaining good morphology and ZnO crystallinity. Publications on microwave-assisted synthesis as chemically green synthesis of chemical product has increased in order to eliminate the generation of hazardous substances and to reduce intensive energy consumption [8,9]. Several issued of different experimental variables over ZnO nanoparticles size, morphology, and physicochemical performances have been studied [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another article, cationic polyacrylamide (CPAM) was synthesized via free solvent cationic polymerization under microwave irradiation and it's exfoliation ability has been evaluated in MMT-acide suspension. It was demonstrated that structure and thermal stability of cationic composite polyacrylamide depend on the ratio of monomer/clay and the temperature optimized [8].…”
mentioning
confidence: 99%
“…There are two articles which focused on Montmorillonite Clay (Maghnite-H+) studies, they are by Medjdoub & Mohammed [7] and Abdelkader & Mohammed [8]. In the first paper, a new synthetic method has been developed to produce HACTP using friendly, green, ecologic and non toxic catalyst clay as proton source, the support catalyst Maghnite-H+.…”
mentioning
confidence: 99%